Forensic Dental Cremation Recovery and Analysis-A Review Article (Global Journal of Medical Research, 2017)
Teeth are amongst the most resilient structures of the human body. The dentition and dental works are commonly preserved, in most cases where the exposure of a body to a heat source and hence becomes a reliable source of the DNA. Dental works such as an implant, restoration, crown etc. are preserved till very high temperatures. An effort has been made to study the main articles on dental cremation recovery and to express it in a systematic manner.
Keywords: forensic odontology; cremation; temperature; recovery